The increase in the proportion of impervious surfaces and changes in air temperature, relative humidity, and cloud cover in Poland - Bartoszek, Krzysztof; Łachowski, Wojciech; Matuszko, Dorota (Quaestiones Geographicae, 2023)
The aim of the study is to characterise the changes in the proportion of impervious surfaces (ISs) in Poland and their impact on changes in temperature, air humidity, and cloud cover. The results of satellite image classification from 1990, 2000, 2010 and 2020, as well as meteorological data from the period 1981–2020 for the warm half of the year, were used. An analysis was performed making it possible to compare the changes in the proportion of ISs in 3 decades, i.e. 1991–2000, 2001–2010 and 2011–2020. In Poland, in the years 1991–2020, the total area of ISs increased by approxi- mately 30%. At the same time, statistically significant positive trends in maximum temperature are visible throughout Poland, ranging from 0.48°C per 10 years to >0.90°C per 10 years. Trends in the magnitude of low-level cloud cover are negative throughout Poland and range from −2.7% to −2.3% per 10 years. The frequency of stratiform clouds is decreasing, while that of mid-level Cirrus and Cumulus clouds is increasing. The results show a relationship between the increase in ISs in Polish cities and changes in meteorological elements in their area and in the immediate vicinity, which were most pronounced in the first decade of the 21st century.